Neurodiversitet, Theory of Mind og tegneserieeksperimenter - Raaby Gammelgaard, Lasse (K&K - Kultur og Klasse, 2025)
This article contributes to discussions of neurodiversity and research on anthropomorphic theory of mind. First, it accounts for neurodiversity scholars’ critique of early cognitive research on Theory of Mind and autism, arguing that this research leads to a pathologizing and othering of neurodivergent experiences. Adopting a neurodiversity paradigm, it is argued that cognitive studies on Theory of Mind can learn from graphic medicine and its narrative testimonies of neurodivergence. A case study of two comic books demonstrates the potential of (autobiographical) comics for portraying neurodivergent experiences, employing the verbal-visual multimodality of the genre. The article proposes that graphic medicine can provide an inside-out perspective of neurodivergence, which can challenge a pathologizing medical position that defines things from a neurotypical position.